(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The research aimed to evaluate the reality of expert systems in their dimensions: hardware, software, and those dealing with the expert system, by surveying the opinions of those concerned in the General Company for the Port of Latakia The researcher relied on the descriptive analytical approach, and the research community included employees at senior administrative levels and executive directors in the company studied. The research sample was a soft sample of (200) administrative members. The researcher distributed (200) questionnaires, and (175) were retrieved. A questionnaire suitable for statistical analysis, with a response rate of (87.5%). The results showed there is0 expert systems in all their dimensions: hardware, software, and those dealing with the expert system in the company under study is a weak reality.